Thiazole Based Carbohydrazide Derivatives as α-Amylase Inhibitor and Their Molecular Docking Study. (4th February 2019) - Taha, Muhammad; Irshad, Maryam; Imran, Syahrul; Rahim, Fazal; Selvaraj, Manikandan; Almandil, Noor Barak; Mosaddik, Ashik; Chigurupati, Sridevi; Nawaz, Faisal; Ismail, Nor Hadiani; Ibrahim, Mohamed
Abstract : In this study we are going to present thiazole based carbohydrazide in search of potent antidiabetic agent as α -amylase inhibitors. Thiazole based carbohydrazide derivatives 1-25 have been synthesized, characterized by 1 HNMR, 13 CNMR, and EI-MS, and evaluated for α -amylase inhibition. Except compound 11 all analogs showed α -amylase inhibitory activity with IC50 values from 1.709 ± 0.12 to 3.049 ± 0.25 μ M against the standard acarbose (IC50 = 1.637 ± 0.153 μ M). Compounds 1, 10, 14, and 20 exhibited outstanding inhibitory potential with IC50 value 1.763 ± 0.03, 1.747 ± 0.20, 1.709 ± 0.12, and 1.948 ± 0.23 μ M, respectively, compared with the standard acarbose. Structure activity relationships have been established for the active compounds. To get an idea about the binding interaction of the compounds, molecular docking studies were done.